PJMHS 2021
DOI: 10.53350/pjmhs211571553
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Platelet Rich Plasma for the Management of Knee Osteoarthritis

Abstract: Aim: To determine impact of platelet rich plasma therapy for the management of knee osteoarthritis. Study design: Prospective double-blinded, add –on randomized, placebo-controlled trial Place and duration of study: Department of Orthopedics, Shaikh Zayed Hospital Lahore from 1st January 2019 to 30th June 2019 Methodology: Fifty volunteer participants fulfilling inclusion criteria were enrolled. One hundred knees of patients were randomly allocated into two groups. Knees were assigned either of the two groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Studies spanned different countries, with two articles each from India (18,26), Taiwan (27,28) and Australia (19,29). One article each was retrieved from the USA (30), Turkey (31), Pakistan (32), Brazil (33), Spain (34), and China (35).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies spanned different countries, with two articles each from India (18,26), Taiwan (27,28) and Australia (19,29). One article each was retrieved from the USA (30), Turkey (31), Pakistan (32), Brazil (33), Spain (34), and China (35).…”
Section: Resultsmentioning
confidence: 99%
“…VAS was the most used outcome in eight of these studies (18,26,29,(31)(32)(33)(34)(35). In total, the number of patients evaluated in the studies that we reviewed were 1859.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment effects in response to IAI regimens are likely affected by the degree of cartilage degeneration. Numerus studies have conducted subgroup analyses stratified by KL grade to identify the efficacy of IAI agents in patients with KOA of varying severity, particularly PRP [ 53 , 84 , 90 , 125 , 126 , 127 , 128 ], HA [ 38 , 90 , 127 , 128 , 129 ], ACS [ 73 ], and MSCs [ 130 ]. These studies have obtained conclusive results indicating that patients who suffer minor cartilage loss or have a low KL grade generally respond well to such IAI agents compared with those that receive a placebo injection or comparative treatment, whereas those who experience more severe cartilage degeneration or have a high KL grade experience less improvement through treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The groups which received PRP showed improvement in patient-reported outcomes (PROs), including in all six high-quality studies that reported Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) 9,12,16,22,32,36 and VAS pain scale scores. 9,12,22,23 No statistically significant improvement was reported for the moderate-quality study. 45 Regarding functional outcomes, PRP did not have any notable effect on cartilage thickness using ultrasonography evaluation 9 or knee strength.…”
Section: Summary Of Findingsmentioning
confidence: 94%